Perancangan Interior Kafe Pada House Of Batman di Surabaya - Patricia Tjahajo; Adi Santosa; Herlin Sri Utami (Intra, 2013)
In development of an era, many have opened businesses especially pertaining to technology. Undergo development technology which is very fast amongother areas. Technology enjoyed by all people, young and old, so it is with batman. Batman is one of a superhero that all people known and is one figure that use high-tech to defeat his enemy. Community of batman need a place to grouping and progress. Then house of batman in Surabaya made to accommodate the activities of the community of Batman that pertaining to batman. The concept that use of advanced technology is used by batman apply to furnitures café also plot of the sequel batman applied to the design of the room.